2022
DOI: 10.29303/jppipa.v8i6.1639
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Practicality of Articulate Storyline Learning Media on Environmental Pollution Materials for Junior High School Students

Abstract: Research has been carried out on the development of Articulate storyline on environmental pollution material. This study aims to test the validity and practicality of the Articulate storyline on environmental pollution material. The development model used in this research is the ADDIE development model up to the implementation stage. The instruments used in this study were validation sheets and student response questionnaires. The results of this study obtained high validity criteria with a value of 0.90. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…The learning media presented to students have to be interesting to the students to help them gain as much valuable knowledge as they can from the media. The media need to attract students' focus and attention to increase the students' literacy or numeracy skills (Heliawati et al, 2022;Istyadji et al, 2022). As indicated by the score of validity of the learning media developed, it can be said that the media is valid and very feasible to be used in the classroom, and very interesting to the students in the classroom.…”
Section: Resultsmentioning
confidence: 99%
“…The learning media presented to students have to be interesting to the students to help them gain as much valuable knowledge as they can from the media. The media need to attract students' focus and attention to increase the students' literacy or numeracy skills (Heliawati et al, 2022;Istyadji et al, 2022). As indicated by the score of validity of the learning media developed, it can be said that the media is valid and very feasible to be used in the classroom, and very interesting to the students in the classroom.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this research seeks to enhance teachers' knowledge and understanding of effective learning media by showcasing the potential and benefits of Articulate Storyline. By building upon the findings of previous studies, this research contributes to the advancement of instructional design and promotes the adoption of innovative and interactive approaches in educational settings; some relevant studies can be found (Ariani, 2020;Hadza et al, 2020;Istyadji et al, 2022;Jubaerudin et al, 2021;Nasution & Darwis, 2021;Nissa et al, 2021;Nugroho & Arrosyad, 2020;Rianto, 2020;Saadah et al, 2022;Yolanda et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…PjBL-STEM has a positive effect on increasing learning motivation and facilitating skills of vocational students in Taiwan (Chiang et al, 2016). Furthermore, Istyadji et al (2022) stated that the application of learning that involves students more actively can increase student learning motivation.…”
Section: Improvement Of Student Motivationmentioning
confidence: 99%